2016
DOI: 10.1080/15257770.2016.1216565
|View full text |Cite
|
Sign up to set email alerts
|

The radiosensitizing effect of fluorocyclopentenyl-cytosine (RX-3117) in ovarian and lung cancer cell lines

Abstract: RX-3117 (fluorocyclopentenyl-cytosine) is a novel cytidine analog currently being evaluated in a Phase Ib clinical trial in cancer patients with solid tumors. The radiosensitizing effect of RX-3117 was studied in A2780 ovarian cancer cells and non-small cell lung cancer cell lines and related to cell survival and the effect on cell cycle and cell cycle proteins. RX-3117 has a schedule-dependent radiosensitizing effect, but only at pre-incubation (dose modifying factors: 1.4-1.8), observed at pulse and fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…RX-3117 and radiation were also used to investigate the cell cycle distribution. RX-3117 and irradiation led to accumulation of cells in G2 and S phase [29]. RX-3117 might be an effective radiosensitizing agent for NSCLC.…”
Section: Effect On Dna Methyltransferasementioning
confidence: 98%
See 2 more Smart Citations
“…RX-3117 and radiation were also used to investigate the cell cycle distribution. RX-3117 and irradiation led to accumulation of cells in G2 and S phase [29]. RX-3117 might be an effective radiosensitizing agent for NSCLC.…”
Section: Effect On Dna Methyltransferasementioning
confidence: 98%
“…RX-3117 has also been evaluated for its radiosensitizing potential. Firstly, using a clonogenic assay, it was demonstrated that pre-incubation of cells with RX-3117 led to a radiosensitizing effect in the majority of the analyzed cell lines [29]. Moreover, RX-3117 had a significant effect on radiation induced-DNA damage with a delayed DNA repair in irradiated cells, after RX-3117 treatment.…”
Section: Effect On Dna Methyltransferasementioning
confidence: 99%
See 1 more Smart Citation
“…Since DNMT1 expression is cell cycle regulated, this raises the question whether RX-3117 induced DNMT1 down-regulation might be a cell cycle effect. Indeed RX-3117 induces some cell cycle proteins (e.g., CHK2 and cdc25), with an arrest in the S and G2M phase), [33] but whether this is related to DNMT1 down-regulation is unlikely because of the different time-span. Altogether re-activation of TSGs may contribute to the elimination of tumor cells, by inhibition of tumor growth, invasion, and controlling metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study underlines the relevance of DNA methylation as a potential biomarker for RX-3117 s anti-tumor activity. However, RX-3117 is also known to cause DNA damage by its incorporation into DNA [4,33]. Usually the induction of DNA damage by a nucleoside analog takes more time, so that the effects on DNA methylation may occur earlier then the DNA damage.…”
Section: Discussionmentioning
confidence: 99%